Marketing Strategy Implementation for Business Plan at Material Handling Rental Services Startup LogisMe - Rosdiana Rosdiana; Rhian Indradewa; Edi Hamdi; Ketut Sunaryanto (Studi Ilmu Manajemen dan Organisasi, 2025)
Purpose: This study aims to analyze the marketing strategies and operational practices of LogisMe, a logistics company focused on material handling. It explores the use of the B2B model, NICE marketing mix, and Porter’s Generic Strategy for market differentiation. Additionally, the research examines customer relationship management, relationship marketing, digital marketing, and employee expertise in enhancing sales effectiveness. Methodology/approach: This research employs a qualitative approach, gathering data from LogisMe’s internal documents, marketing strategies, and operational plans. A case study method is used to gain an in-depth understanding of the company's marketing practices. Data were collected through interviews with key management personnel and analyzed using the Sales Effectiveness Drivers framework, which consists of five elements: definer, shaper, exciter, enlightener, and controller drivers. Each of these elements was assessed to determine their impact on LogisMe’s sales force structure and marketing strategies. Results/findings: The study reveals that LogisMe successfully leverages its B2B model by employing the NICE marketing mix strategy to foster strong business networks and customer engagement. By focusing on specific market segments and utilizing Porter’s differentiation strategy, LogisMe has been able to carve a niche in the logistics industry. The company’s investment in skilled employees, digital marketing, and relationship marketing further contributes to its sales effectiveness. The Sales Effectiveness Drivers framework has helped LogisMe optimize its sales force structure and activities, resulting in improved operational efficiency and market competitiveness. Limitations: The study is limited to LogisMe’s current operations and marketing strategies, which may not fully capture long-term trends or challenges in the logistics and warehousing sector. Additionally, the research is based on qualitative data from a single company, which may limit the generalizability of the findings to other logistics firms or industries. Contribution: This research contributes to the understanding of how B2B companies in the logistics industry can use strategic marketing and operational frameworks to enhance their sales effectiveness and competitiveness. It provides a practical application of the NICE marketing mix, Porter's Generic Strategy, and the Sales Effectiveness Drivers framework in the context of logistics and warehousing. The study offers valuable insights for other companies aiming to differentiate themselves and optimize their sales and marketing efforts Novelty: The novelty of this study lies in its exploration of the NICE marketing mix in a B2B logistics setting, combined with the use of the Sales Effectiveness Drivers framework. This integration provides a unique perspective on how logistics companies can align their marketing and sales strategies with organizational goals to achieve differentiation and enhance customer relationships in a competitive market.